Comparison of fluid balance between competitive swimmers and less active adolescents - Higham, D. G.; Naughton, G. A.; Burt, L. A.; Shi, X. (International Journal of Sport Nutrition and Exercise Metabolism, 2009)
The aim of this study was to compare daily hydration profiles of competitive adolescent swimmers and less active maturation- and sex-matched controls. Hydration profiles of 35 competitive adolescent swimmers (male n = 18, female n = 17) and 41 controls (male n = 29, female n = 12) were monitored on 4 consecutive days. First morning hydration status was determined independently by urine specific gravity (USG) and urine color. Changes in fluid balance were estimated during the school day and in training sessions after adjusting for self-reported urine losses and fluid intake. Urinalyses revealed consistent fluid deficits (USG >1.020, urine color =5) independent of activity group, sex, and day of testing (hypohydration in 73-85% of samples, p > .05). Fluid balance and intake were observed over typical school days in males and females from the 2 groups. During training, male swimmers lost more fluid relative to initial body mass but drank no more than females. Although both activity groups began each testing day with a similar hydration status, training induced significant variations in fluid balance in the swimmers compared with controls. Despite minimal fluid losses during individual training sessions (<2% body mass), these deficits significantly increased fluid needs for young swimmers over the school day.